Pelvic Floor Muscle Anatomy and its Contribution to Penile Erection in Olive Baboons - Roman Ovchinnikov; Ilya Pyatnitskiy (Urology Research and Practice)
Objective: Despite the number of studies on the contribution of pelvic floor muscles (PFM) to the penile erection process, their significance is still underestimated. The goal of this study was to investigate the role of PFM in the erection process in non-human primates.